Police personnel stress during COVID-19 pandemic lockdown in Kano, Nigeria - Ndubueze, Philip N. (International journal of police science & management, 2024)
Police personnel experience stress in the course of their routine duties. Although this stress is considered normal, given the risky nature of the job, it is exacerbated by increasing demands for law and order during pandemic-induced lockdowns. This study was designed to examine the sources/nature and effects of stress among police personnel during the SARS-CoV2 (COVID-19) pandemic lockdown and how police officers treated and managed it. The qualitative study used a phenomenological design to collect data from 30 purposively selected police personnel of Kano State Police Command, Nigeria, through in-depth interviews. Results showed that most of the participants experienced stress during lockdown. The stress emanated from a lack of cooperation by defiant members of the public who flouted the restrictions of movement order, the increased work schedule/workload, fear of being infected with the virus and a lack of understanding from families/friends. In addition, some participants reported that they experienced depression, anxiety or post-traumatic stress disorder and suicidal thoughts as a result of the stress they faced. Nonetheless, most participants reported that the availability of support from family members, peer support and trust, physical exercise, talking about occupational stress with peers/superiors, making time for their hobbies, eating well, taking a deep breath, meditation and prayers helped them relieve the occupational stress. These findings provide useful insights into the dynamics of police personnel stress and its management in the era of COVID-19 pandemic lockdown in a state in Africa's most populous country, Nigeria.